2021
DOI: 10.3389/fnhum.2021.602723
|View full text |Cite
|
Sign up to set email alerts
|

Neural Kinesthetic Contribution to Motor Imagery of Body Parts: Tongue, Hands, and Feet

Abstract: Motor imagery (MI) is assimilated to a perception-action process, which is mentally represented. Although several models suggest that MI, and its equivalent motor execution, engage very similar brain areas, the mechanisms underlying MI and their associated components are still under investigation today. Using 22 Ag/AgCl EEG electrodes, 19 healthy participants (nine males and 10 females) with an average age of 25.8 years old (sd = 3.5 years) were required to imagine moving several parts of their body (i.e., fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 79 publications
3
9
0
Order By: Relevance
“…The familiar and abstract objects were image entities in a real environment but virtual (disembodied) in augmented reality. Note also that in the augmented reality atmosphere, objects, by construction, are virtual and incorporated into a real environment [ 3 , 15 , 16 ]. This suggest that the bilateral gamma posterior network would be more involved in imagery and execution tasks involving virtual objects, that is, better synchronised for tasks associated with virtual objects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The familiar and abstract objects were image entities in a real environment but virtual (disembodied) in augmented reality. Note also that in the augmented reality atmosphere, objects, by construction, are virtual and incorporated into a real environment [ 3 , 15 , 16 ]. This suggest that the bilateral gamma posterior network would be more involved in imagery and execution tasks involving virtual objects, that is, better synchronised for tasks associated with virtual objects.…”
Section: Discussionmentioning
confidence: 99%
“…real and virtual environments [ 12 ]. Creative ideation naturally relies on mental and cognitive simulation [ 13 ], which requires the intervention of internal imagery [ 14 ] and allows the representations of visual, motor and/or verbal actions to arise [ 15 , 16 ]. Such an approach is assisted by abundant scientific literature that describes and validates the neurocognitive overlapping between the mental simulation of an action and the action itself [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The training phase aimed to familiarise each participant with the experimental paradigm. The experimental paradigm was a repetition of visual cue-based synchronous trials of different motor imagery tasks 4 , 47 – 49 . In accordance with this paradigm (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Building on from the “simulation hypothesis”, accumulating evidence suggests that motor imagery (MI), which encompasses a cognitive representation of an actual movement has similar neural correlates to those of real movement 2 . MI of distinct body parts simultaneously actuates and engages the equivalent sensorimotor and somatosensory cortices, including kinaesthetic information 3 , 4 . Empirical evidence for the existence of neural networks has focused particularly on signals associated with frontal (supplementary motor area, motor cortex, dorsolateral premotor cortex, inferior frontal gyrus), and parietal areas (primary somatosensory gyrus, superior and inferior parietal regions including vestibular cortex) 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…kinesthetic illusion will complement the relevant loop. Neuroimaging studies have revealed that a relationship exists between the movement that has been imagined and the activation patterns of somatotopically organized motor and kinesthetic areas ( Giannopulu and Mizutani, 2021 ). In the upper-limb MI-BCI study, KI induced by rubber hand can significantly amplify EEG features and provide better guidance to enhance upper-limb MI ( Song and Kim, 2019 ).…”
Section: Introductionmentioning
confidence: 99%